Microstructure–conductivity relationship of Na3Zr2(SiO4)2(PO4) ceramics. Issue 3 (23rd August 2018) - Naqash, Sahir; Sebold, Doris; Tietz, Frank; Guillon, Olivier
Abstract: The ionic conductivity of solid electrolytes is dependent on synthesis and processing conditions, ie, powder properties, shaping parameters, sintering time ( t s ), and sintering temperature ( T s ). In this study, Na3 Zr2 (SiO4 )2 (PO4 ) was sintered at 1200 and 1250°C for 0‐10 hours and its microstructure and electrical performance were investigated by means of scanning electron microscopy and impedance spectroscopy. After sintering under all conditions, the sodium super‐ionic conductor‐type structure was formed along with ZrO2 as a secondary phase. The microstructure investigation revealed a bimodal particle size distribution and grain growth at both T s . The density of samples increased from 60% at 1200°C for 0 hours to 93% at 1250°C for 10 hours. The ionic conductivity of the samples increased with t s due to densification and grain growth, ranging from 0.13 to 0.71 mS/cm, respectively. The corresponding equivalent circuit fitting for the impedance spectra revealed that grain boundary resistance is the prime factor contributing to the changing conductivity after sintering. The activation energy of the bulk conductivity ( E a, bulk ) remained almost constant (0.26 eV) whereas the activation energy of the total conductivity ( E a ) exhibited a decreasing trend from 0.37 to 0.30 eV for the samples with t s  = 0 and 10 hours, respectively—both sintered at 1250°C. In this study, the control of the grain boundaries improved the electrical conductivity by a factor of 6.